How to measure adherence to a Mediterranean diet in dental studies: is a short adherence screener enough? : a comparative analysis - Bartha, Valentin; Exner, Lea; Meyer, Anna-Lisa; Basrai, Maryam; Schweikert, Daniela; Adolph, Michael; Bruckner, Thomas; Meller, Christian; Wölber, Johan; Wolff, Diana (Nutrients, 2022)
This study aimed to evaluate the Mediterranean Diet Adherence Screener (MEDAS) in a study investigating the anti-inflammatory effect of a 6-week Mediterranean diet intervention on periodontal parameters. Data from a randomized clinical trial were analyzed for correlations between the MEDAS score and oral inflammatory parameters (bleeding on probing (BOP), gingival index (GI), and periodontal inflamed surface area (PISA)) and select nutrient intakes estimated by a food frequency questionnaire (FFQ) and a 24-h dietary recall (24dr). A mixed model, calculations of Spearman ρ, Lin’s Concordance Coefficient (CC), and Mann-Whitney U test were used for the statistical analyses. The MEDAS score was significantly negatively correlated with periodontal inflammation (BOP: CoE −0.391, p < 0.001; GI −0.407, p < 0.001; PISA −0.348, p = 0.001) and positively correlated with poly unsaturated fatty acids/total fat, vitamin C, and fiber intake estimates obtained from the FFQ and 24dr (ρ 0.38-0.77). The FFQ and 24dr produced heterogeneously comparable intake results for most nutrients (CC 0-0.79, Spearman ρ 0.16-0.65). Within the limitations of this study, the MEDAS was able to indicate nutritional habits associated with different levels of periodontal inflammation. Accordingly, the MEDAS can be a sufficient and useful diet screener in dental studies. Due to its correlation with oral inflammatory parameters, the MEDAS might also be useful in dental practice.